The gut–lung axis in asthma: microbiota-driven mechanisms and therapeutic perspectives - Yang, Zihan; Mao, Wei; Wang, Junyang; Yin, Leyi (Frontiers in Microbiology, 2025)
Asthma is a multifactorial inflammatory airway disease shaped by complex interactions among host genetics, environmental exposures, and the microbiota. The human body hosts a highly diverse microbial ecosystem, comprising more than 10,000 species that profoundly influence host physiology through the regulation of nutrient metabolism and immune homeostasis. Disruption of this balance, or dysbiosis, contributes to the onset and progression of immune-mediated diseases, including asthma. Asthma is a multifactorial disorder driven by the complex interaction of genetic susceptibility and environmental exposures, and its heterogeneous phenotypes and severity are increasingly associated with alterations in the microbiota. In particular, the gut–lung axis represents a critical bidirectional pathway through which microbial communities and their metabolites in the gut and airways shape immune responses and respiratory health. This review summarizes current evidence on microbiota-driven mechanisms underlying asthma pathogenesis, highlights the role of the gut–lung axis in immune regulation, and discusses emerging microbiota-targeted therapeutic strategies, emphasizing their potential for clinical translation in asthma treatment.